(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article discusses one of the primary issues that affects both adolescents and adults, namely "drugs," which is a chemical that modifies the physical functioning of a person’s body, affecting their mental health and is deemed deadly to society. This has an impact on the mind’s psychological functioning as well. This article focuses on the effects that drugs have on people’s lives and on society as a whole. We read about different incidences of individuals consuming drugs in newspapers, social media, and on television, and we often hear about illicit substances being confiscated from their homes. The article focuses on the Narcotics Drugs and Psychotropic Substances Bill, which was passed in 1985. It also discusses the signs and symptoms of addiction, as well as the penalties that can be imposed when caught with drugs, which include prison sentences of up to ten years and fines of up to one lakh dollars depending on the quantity. Drugs have had a negative influence on civilization since the beginning of time. This article also discusses drug addiction, which may ruin a person’s life and lead to criminal activity. There have been several examples of persons being arrested in the act of drug trafficking and drug usage, both of which can cause mental illness. In recent years, the majority of Bollywood superstars have been caught up in drug scandals, many of which have come to light. As a result, narcotics have the potential to cause crime and disrupt society’s peaceful order. Drug usage has an impact not only on the individuals who use it, but also on their families. Finally, the essay emphasizes the relevance of NCB as well as the effects of various types of medications on individual mental health.